Development of Inventory Management System in a Total Productive Maintenance Environment - Lim, Benedict Chin Khian (2004)
Implementation of Total Productive Maintenance (TPM) is increasingly being seen as a suitable initiative or technique for effectively involving the workforce in manufacturing based organizations to increase productivity with the support of both effective and efficient maintenance works as well as inventory management system. The aim of this research is concerned with the development of a computerize inventory management system using Microsoft Visual Basic 6.0. This improvement is to replace present manual paperwork procedure towards the implementation of TPM and IS014000. The proposed system attempts to achieve this by providing a database for parts information storage with search function, ability to record each inventory transactions in real time, calculating material requirement planning (MRP), create Bill Of Materials (BOM) and making purchase order (PO). This research also includes the evaluation of the system on real data from the company. The data shows that this system produced correct result and reduce the time spend on data searching by 80.4% or increase the manpower efficiency by 510%. These results show that this system can lead to increase the controllability and monitoring of inventory, and increase manpower efficiency.